2006
DOI: 10.1063/1.2181807
|View full text |Cite
|
Sign up to set email alerts
|

Convective flows in a two-layer system with a temperature gradient along the interface

Abstract: The nonlinear stability of two superposed horizontal liquid layers bounded by two solid planes and subjected to a horizontal temperature gradient, is investigated. Two types of boundary conditions, periodic boundary conditions and heat-insulated lateral walls, are considered. The nonlinear simulations of the wavy convective regimes for a particular set of fluids, are performed. The dependence of the direction of the wave propagation depends on two factors, which are studied, the ratio of the layers thicknesses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…Therefore, eqs. (84)−(87) are the same as the results obtained by Nepomnyashchy and Simanovskii [17].…”
supporting
confidence: 74%
See 1 more Smart Citation
“…Therefore, eqs. (84)−(87) are the same as the results obtained by Nepomnyashchy and Simanovskii [17].…”
supporting
confidence: 74%
“…A linear perturbative analysis with respect to two-dimensional and three-dimensional perturbations revealed the existence of three kinds of patterns: wave propagation from the cold to the hot regions or in the opposite direction or still stationary longitudinal rolls. Nepomnyashchy and Simanovskii [17,18] investigated the nonlinear stability of the same two-layer system and concluded that the direction of the wave propagation depended on the ratio of the layers thicknesses and the Marangoni number. Although the existing literatures on square cavities are rich, the investigations concerned with annular cavities are fairly limited.…”
Section: Introductionmentioning
confidence: 98%
“…Here f (x,y) is a periodic function that describes the topographic patterns decorated on the substrate surface. The evolution equations thus obtained shown below describe the stability, dynamics and morphology of the liquid-air interface (i = 2) and the liquid-liquid interface (i = 1) (Danov et al 1998a, b;Pototsky et al 2006;Nepomnyashchy and Simanovskii 2006a, b, 2007, 2009aFisher and Golovin 2005):…”
Section: Equations Of Evolutionmentioning
confidence: 99%
“…The effective pressures at the liquid-liquid and liquid-air interfaces are derived from the normal stress balances at the respective interfaces as (Danov et al 1998a, b;Bandyopadhyay et al 2005Bandyopadhyay and Sharma 2006;Pototsky et al 2006;Nepomnyashchy and Simanovskii 2006a, b, 2007, 2009aFisher and Golovin 2005):…”
Section: Equations Of Evolutionmentioning
confidence: 99%
See 1 more Smart Citation